THE INFLUENCE OF ORGANIZATIONAL COMMITMENT TOWARDS JOB SATISFACTION AMONG POLYTECHNIC STAFF - Muhamad Saufiyudin Omar; Nurasyikin Mohd Salleh; Siti Fatimah Abdul Aziz (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Organizational commitment is identified as a critical factor that is closely associated with job satisfaction. A limited number of studies have been done to look into the influence of organizational commitment on job satisfaction among Polytechnic staff. Therefore, this study aims to examine the influence of organizational commitment and job satisfaction. A quantitative study was conducted, and stratified random sampling was employed to collect data. Questionnaires were distributed and answered by 130 respondents. The findings reveal that organizational commitment that comprises normative commitment, continuance commitment and affective commitment significantly and positively impacts job satisfaction. This suggests that improving the organizational commitment, more specifically, the normative commitment, continuance commitment, and affective commitment among Polytechnic staff is critically important to enhance their job satisfaction.